2015
DOI: 10.1124/dmd.115.064170
|View full text |Cite
|
Sign up to set email alerts
|

Solute Carrier Family of the Organic Anion-Transporting Polypeptides 1A2– Madin-Darby Canine Kidney II: A Promising In Vitro System to Understand the Role of Organic Anion-Transporting Polypeptide 1A2 in Blood-Brain Barrier Drug Penetration

Abstract: Organic anion-transporting polypeptide (OATP) 1A2 has the potential to be a target for central nervous system drug delivery due to its luminal localization at the human blood-brain barrier and broad substrate specificity. We found OATP1A2 mRNA expression in the human brain to be comparable to breast cancer resistance protein and OATP2B1 and much higher than P-glycoprotein (P-gp), and confirmed greater expression in the brain relative to other tissues. The goal of this study was to establish a model system to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 45 publications
3
39
0
Order By: Relevance
“…OATP1A2 is abundantly located in the epithelium of many tissues and influences the disposition of numerous drugs, xenobiotics, and endobiotics (Kullak-Ublick et al, 1995;Steckelbroeck et al, 2004;Liu and Li, 2014). At the apical membrane of renal tubular cells, OATP1A2 mediates the reabsorption of xenobiotics (Lee et al, 2005); in the biliary epithelium, OATP1A2 facilitates the excretion of xenobiotics into bile; and at the luminal membrane of the blood-brain barrier, OATP1A2 modulates the uptake of opioid analgesic peptides and other central nervous system-active agents into the brain (Liu et al, 2015). More recently, OATP1A2 has been detected on the apical membrane of the retinal pigment epithelium, where it facilitates the uptake of retinoids (Chan et al, 2015b;Gao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…OATP1A2 is abundantly located in the epithelium of many tissues and influences the disposition of numerous drugs, xenobiotics, and endobiotics (Kullak-Ublick et al, 1995;Steckelbroeck et al, 2004;Liu and Li, 2014). At the apical membrane of renal tubular cells, OATP1A2 mediates the reabsorption of xenobiotics (Lee et al, 2005); in the biliary epithelium, OATP1A2 facilitates the excretion of xenobiotics into bile; and at the luminal membrane of the blood-brain barrier, OATP1A2 modulates the uptake of opioid analgesic peptides and other central nervous system-active agents into the brain (Liu et al, 2015). More recently, OATP1A2 has been detected on the apical membrane of the retinal pigment epithelium, where it facilitates the uptake of retinoids (Chan et al, 2015b;Gao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Since differences between human and rodent isoforms of the transport proteins expressed by ECs mean that certain compounds can be substrates for the human isoform, but not for the rodent counterpart, it is important to use cells of human origin for BBB models to get results that translate to human safety (Liu et al 2015).…”
Section: Models Of the Blood-brain Barrier (Bbb)mentioning
confidence: 99%
“…Also, due to the presence of some nonconserved histidine residues in the human sequence, TLR4 triggers for instance contact hypersensitivity to nickel in humans, but not in mice (Schmidt et al 2010). Differences in the primary sequences between orthologs can also lead to differences in the selectivity of the transport proteins of the blood-brain barrier leading to differences in the uptake of certain compounds (Liu et al 2015).…”
mentioning
confidence: 99%
“…MDCKII-WT cells express canine P-gp but not BCRP. In addition, endogenous P-gp expression can be impacted by BacMam virus load (Liu et al, 2015). In previous studies, the BCRP-expressing in vitro transwell system was not found to be predictive of in vivo transport activity (Enokizono et al, 2008;Zhao et al, 2009), likely because P-gp/BCRP cosubstrates were included and the activity of endogenous P-gp was ignored.…”
Section: Discussionmentioning
confidence: 98%